(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, the study of the emergence and development of urbanization in the territory of ancient Khorezm is analyzed in the work of researchers. The history of the study of urban processes in Khorezm based on archaeological and written sources is described. Controversial issues related to the study of urbanization processes are analyzed.